Studi Kasus: Asuhan Keperawatan pada Pasien Fraktur Tertutup dengan Gangguan Rasa Aman Nyaman Nyeri Melalui Tindakan Pemberian Kompres Dingin Di Rumah Sakit TK II Putri Hijau Medan - Septiani, Tri Andini; Olivia, Nina; Sayfrinanda, Virginia (Lembaga Publikasi Ilmiah Nusantara, 2023)
A closed fracture is a several severing of bone tissue that is not accompanied by injury to the outside caused by trauma or injury that causes pain so that the individual feels an uncomfortable sensation and may interfere with daily activities. The administration of analgesics is the choice of many patients to overcome pain, one of the non-pharmacological therapies that can be given is the administration of cold compresses / ice. The purpose of the study was to determine the reduction in pain of closed fracture patients through the act of giving cold compresses. This research method is a case study that includes assessment, diagnosis, intervention, implementation (giving cold compresses during pain appears) and evaluation, the subjects used are 2 closed fracture patients with a pain scale of 6. The results of the case study showed that before cold compresses were performed on both patients, closed fractures with a pain scale of 6, after giving cold/ice compresses with a temperature of 15⁰C for 10 minutes, the patient's pain was reduced to a pain scale of 3 (0-10). In conclusion, the researchers concluded that Nursing care in closed fracture patients with cold compresses can reduce pain intensity.